China - Biomass Cogeneration Development Project : Fuel Supply Handbook for Biomass-Fired Power Projects - World Bank (World Bank, 2012)
This handbook provides an overview of the main topics that need consideration when managing the supply of biomass to large biomass power plants. It will help investors in China to develop, with assistance of local biomass supply experts, their own solutions. The focus is on biomass residues, in particular agricultural residues (mainly straw and stalks) and forestry residues (mainly residues from forestry operations). This handbook covers a wide range of topics related to biomass fuel supply risk in the planning and preparation stages for a biomass-fired power plant. Chapter two introduces the use of biomass as an energy source, including fuel selection considerations and the fuel standards and specifications required to match a particular fuel supply to a power generation system. Chapter three describes the use of biomass resource assessments at the project planning stage. Chapters four and five give insight into the biomass supply from straw and forestry residues, respectively. Finally, fuel supply management is covered in chapter six, which addresses the topics to be considered both at the plant planning stage and at the operational stage. It describes a methodological approach for fuel inspection and quality control, as well as an instrument for assessing fuel supply risks and developing mitigation strategies.